Linguocultural Characteristics of Scientific Activity Object Domain in Critical Remarks in English Research Articles - Balatska, Olena; Saienko, Larysa; Babash, Larysa; Moskalenko, Maryna (International Journal of Engineering and Technology, 2018)
The article examines linguocultural characteristics of SCIENTIFIC ACTIVITY object domain in critical remarks in English research articles considered to be the leading genre of scientific discourse.  The methods used in the research include cognitive-discursive interpretation method, text-interpretation analysis,  and quantitative analysis.  The problem has been studied in a corpus of 1027 critical remarks including 2268 critical utterances registered in 350 English-language research articles from ten scientific disciplines. The article presents classification of critical remarks developed on the basis of components of scientific activities which include PROBLEM / TOPIC, THEORY, METHODOLOGY, DATA, RESULTS, CONCLUSIONS, TEXT, HYPOTHESIS, and RESEARCH. Percentage of using every object of criticism has been calculated. It has been found out that verbalization of every type of criticism varies and is influenced by the group factor.